Current Status of Gene Expression Profiling to Assist Decision Making in Stage II Colon Cancer. (28th May 2014) - Chee, Cheng E.; Meropol, Neal J.
Abstract: The decision regarding adjuvant therapy for patients with stage II colon cancer remains a challenge. In contrast to stage III colon cancer, for which compelling clinical data support the use of adjuvant chemotherapy, the clinical benefit of systemic therapy in unselected patients with stage II disease is modest at best. Risk stratification based on clinicopathologic features and DNA mismatch repair status is commonly used in adjuvant therapy decisions, but these factors do not have a desired level of precision in identifying patients at high risk. Recently, gene expression platforms have been developed to further define risk and to assist in therapeutic decision making for patients with stage II disease. This review describes those platforms that are furthest along in clinical development, in an effort to place their potential clinical application in context. Abstract : Gene expression platforms have been developed to further define risk and to assist in therapeutic decision making for patients with stage II colon cancer. This review describes those platforms that are furthest along in clinical development, in an effort to place their potential clinical application in context.